SPANISH TEACHER TRAINING IN BRAZIL: THE CHALLENGES TOWARDS FLUENCE IN A SECOND LANGUAGE - Santos Carvalho, Regivaldo (Revista Gênero e Interdisciplinaridade, 2023)
Prepared from a Bibliographic Review, the objective of this article is to discuss the training of Spanish language teachers in Brazil and the challenges of achieving fluency in a second language. Specifically, this article addresses the historical aspects of the Spanish Language in Brazil, problematizes the current legislation on the subject, criticizes the status of an optional subject relegated to the Spanish Language and discusses the importance of this language for Brazilian culture and society. As for the methodological approach, the bibliographical research is qualitative and descriptive in nature. The literature survey was carried out between the months of February and March 2022 in the Scielo and Google Scholar databases, using descriptors and their combinations in Portuguese: the challenges to Spanish teacher training”; “training of Spanish teachers in Brazil”; “Challenges to learning and teaching the Spanish Language”. Articles were selected between 2011 and 2021, published in Portuguese and made available free of charge on the internet. The results highlighted the contrast between the sociocultural dimension of the Spanish Language and its devaluation within the scope of Basic Education. It was concluded that teacher training is still marked by theoretical-pedagogical limitations and social discredit.